A pilot study on the preventative potential of alpha-cyclodextrin and hydroxytyrosol against SARS-CoV-2 transmission - Ergoren, Mahmut Cerkez; Paolacci, Stefano; Manara, Elena; Dautaj, Astrit; Dhuli, Kristjana; Anpilogov, Kyrylo; Camilleri, Giorgio; Suer, Huseyin Kaya; Sayan, Murat; Tuncel, Gulten; Sultanoglu, Nazife; Farronato, Marco; et al. (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the current pandemics. This virus attacks the cells by binding to the transmembrane angiotensin I converting enzyme 2. In this study, we experimented a food supplement containing alpha-cyclodextrin and hydroxytyrosol for the improvement of the defenses against the SARS-CoV-2. Hydroxytyrosol has anti-viral properties and is able to reduce the serum lipids in mice. α-cyclodextrin has the ability to deplete sphingolipids and phospholipids from the cellular membranes. The aim of the present preliminary open non-controlled interventional study was to evaluate the efficacy of alpha-cyclodextrin and hydroxytyrosol in improving defenses against SARS-CoV-2. Methods: Fifty healthy volunteers at a higher risk of SARS-CoV-2 infection from Northern Cyprus and six positive individuals for SARS-CoV-2 were enrolled in this study. The in silico prediction was performed using D3DOCKING to evaluate the interactions of hydroxytyrosol and alpha-cyclodextrin with proteins involved in the SARS-CoV-2 endocytosis. Results: The 50 volunteers did not become positive in 15 days for SARS-CoV-2 after the administration of the compound for two weeks, despite they were at higher risk of infection than the general population. Interestingly, in the cohort of six positive patients, two patients were administered the spray and became negative after five days, despite the viral load was higher in the treated subjects than the untreated patients who became negative after ten days. In addition, we identified possible interactions among hydroxytyrosol and alpha-cyclodextrin with the protein Spike and the human proteins ACE2 and TMPRSS2. Conclusions: We reported on the results of the possible role of alpha-cyclodextrin and hydroxytyrosol in improving defenses against SARS-CoV-2. The next step will be the administration of the compound to a larger cohort in a controlled study to confirm the reduction of the infection rate of SARS-CoV-2 in the treated subjects.